Engineering approach to calculate the effective permeability of a composite material with unbiased ferrimagnetic nanoparticles - Kyriakou, John G; Chryssomallis, Michael T (IET microwaves, antennas & propagation, 2017)
A step-by-step engineering approach offering a model for the characterization of magnetic composite materials is presented. The modelling of composite materials containing unbiased ferrites is a subject of great interest, due to extended range of applications, such as hyperthermia and microwave absorbers. Here, unbiased ferrites simplify the application structure, as they do not require a biasing field, while they can resonate at low microwave frequencies due to their innate magnetocrystalline anisotropy field. However, so far there has not been an explicit organized step-by-step engineering modelling approach. The homogenization approximation formula is used in conjunction with Landau–Lifshitz–Gilbert equation solution to systematically compute the complex effective permeability and compare it with published measurements, from an engineer's result-focused perspective. For further validation, simulations of these composite materials as periodic structures are carried out, which additionally provide useful insight on the electromagnetic field distributions within the composites and are often more accurate. The results of the proposed procedure show good agreement with the experimental ones, which validate it, while the relatively greater error appears for the imaginary parts. The EM field distributions suggest that better focusing around the nanoparticles is achieved when those are large enough to form magnetic domains.